Optimizing Transfer Pricing And Capital Intensity Strategies In Reducing Tax Burden: A Study On Multinational Companies - Febri Tiara Finola (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of Transfer Pricing and Capital Intensity on Tax Avoidance in multinational manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The study uses a quantitative method with secondary data obtained from the financial statements of multinational manufacturing companies. The analysis was conducted using panel data regression to evaluate the effect of Transfer Pricing and Capital Intensity on Tax Avoidance, with the help of Eviews software for statistical processing. The results of the study indicate that Transfer Pricing does not have a significant effect on Tax Avoidance, because many companies in the sample conduct domestic affiliate transactions, so they cannot take advantage of differences in tax rates between countries. Conversely, Capital Intensity has a significant effect on Tax Avoidance, because companies with high capital investment in fixed assets can benefit from tax deductions through depreciation. In addition, when Transfer Pricing and Capital Intensity are analyzed together, both affect Tax Avoidance, allowing companies to take advantage of weaknesses in tax regulations.